2005
DOI: 10.1093/aje/kwi343
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Occupation and Amyotrophic Lateral Sclerosis Mortality

Abstract: Occupational exposures are suspected of contributing to the risk of amyotrophic lateral sclerosis (ALS), but results of epidemiologic studies have been inconsistent. The authors prospectively assessed the relation between occupation and ALS mortality among more than 1 million participants in the Cancer Prevention Study II of the American Cancer Society. Follow-up from 1989 through 2002 identified 507 ALS deaths among men and 430 among women. Adjusted rate ratios were calculated by using Mantel-Haenszel weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 47 publications
1
62
4
Order By: Relevance
“…Some of them have associated certain work activities with an increased risk for the disease, like football players and war veterans 19,20 . Others activities that have been associated with sALS risk factor are veterinarians, health workers, athletes, hairdressers, power-production plant workers and electricians 21,22 . In our series, we used the International Standard Classification of Occupation (ISCO), which is a coding system that classifies jobs into occupational groups according to similarity in skill levels and specialization of tasks and duties performed.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have associated certain work activities with an increased risk for the disease, like football players and war veterans 19,20 . Others activities that have been associated with sALS risk factor are veterinarians, health workers, athletes, hairdressers, power-production plant workers and electricians 21,22 . In our series, we used the International Standard Classification of Occupation (ISCO), which is a coding system that classifies jobs into occupational groups according to similarity in skill levels and specialization of tasks and duties performed.…”
Section: Discussionmentioning
confidence: 99%
“…Exact logistic regression was performed to explore the association of exposure to individual metals and pesticides with risk of ALS. Earlier studies have suggested a relationship between education and ALS; therefore, final conditional logistic regression models were fit adjusting for smoking (ever vs. never) and education (high school or less vs. more than high school) [26,27]. SPSS (Statistical Package for the Social Sciences) version 19 (IBM, Chicago, Ill., USA) and SAS (Statistical Analysis System) version 9.3 (SAS Institute Inc., Cary, N.C., USA) were used to conduct all statistical analyses [36,37].…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between exposure to pesticides, agricultural occupations and residing in a rural area and risk of ALS has been inconsistent as only about half of the epidemiologic studies, including two meta-analyses, have found an association [14,20,21,22,23,24,25]. However, this finding has not been replicated by some studies [26,27,28,29]. The association of occupational electromagnetic field exposure with ALS has also been investigated, with most published reports indicating a positive relationship [30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ALS has appeared associated with heavy manual work, electric trauma, and employment in the plastic industry, exposure to heavy metals, acids and animal carcasses, high increased exercises as seen in soccer players in Italy 11,12 . Besides genetic and environmental factors, the existence of a yet-unidentified transmissible agent cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%